99mTc-2-Methoxy-lsobutyl-Isonitril in der Diagnostik der koronaren Herzkrankheit: Ergebnisse einer Multizenterstudie - Höffken, H.; Joseph, K.; Alexander, C.; Bauer, R.; Berberich, R.; Bischof-Delaloye, A.; Böttger, I.; Botsch, H.; Büll, U.; Delaloye, B.; Eichstädt, H.; Eißner, D.; Feine, U.; Feistel, H.; Fischer, M.; Gebhardt, U.; Hahn, K.; Heidenreich, P.; Hundeshagen, H.; Knapp, W. H.; Krause, T.; Kropp, J.; Larock, M. P.; Leisner, B.; Locher, J. T.; Lottes, G.; Löwenstein, O.; Müller, S.; MüllerSchauenburg, W.; Reiners, C.; Riccabona, G.; Rigo, P.; Schober, O.; Schümichen, C.; Schwarzrock, R.; Seybold, K.; Vogt, G.; Wolf, F.; Zech-mann, W. (Nuklearmedizin - NuclearMedicine, 1990)
A total of 226 patients was studied in a phase-Ill multicenter trial to compare the results of stress/rest 99mTc-MIBI with 201TI scintigraphy and/or coronary arteriography. The evaluation of planar and SPECT imaging was based on a semiquantitative visual scoring. A congruent diagnosis was generated from all planar 201TI and 99mTc-MIBI scintigrams performed in 36 patients. In 62 of 63 patients, SPECT-studies with 99mTc-MIBI and 201TI led to an identical diagnosis. In one patient a positive result was obtained with 201TI-SPECT whereas 99mTc-MIBI was negative. Segmental agreement for 1509 SPECT segments was 85.7%, for 554 planar segments it was 86.6%. In comparison to coronary arteriography, performed in 180 patients, the overall sensitivity for the correct diagnosis of coronary artery disease (CAD) was 86% for planar MIBI scintigraphy or 92% for MIBI-SPECT. Overall specificity was 100% for planar imaging and 57% for SPECT. The low specificity of MIBI-SPECT was probably due to high prevalence of CAD in this study population. In a subgroup of 43 patients, who underwent coronary angiography, identical results were found with 99mTc-MIBI and 201TI. Only one patient showed a positive scintigraphic result with both 99mTc-MIBI and 201TI without angiographically proven stenosis greater than 50% or prior myocardial infarction. Vessel sensitivities in stenosed coronary arteries (>50% stenosis) were 54% for the LAD and 87% for the RCX/RCA areas with MIBI-SPECT, or 51 % or 79% for planar scintigraphy, respectively. Vessel specificities for SPECT were 65% in the U\D or 52% in the RCX/RCA, or 90% or 83% in planar imaging. According to the results of this study, 99mTc-MIBI is of the same diagnostic value as 201TI in nuclear cardiology. Scintigraphy with both radiopharmaceuticals correlates well with the diagnosis of CAD. Therefore, 99mTc-MIBI might be an effective substitute for 201TI for myocardial perfusion scintigraphy.